Purchasing Power Parity Influence on Real Exchange Rate Behavior in Romania - Nicolae Ghiba (CES Working Papers, 2011)
Purchasing Power Parity (PPP) represents a fundamental concept in exchange rate modeling. The main idea is given by equality between prices in two different countries when expressing in the same currency. This paper aims to analyze the behavior of real exchange rate between EURO and Romanian new leu (RON) under PPP paradigm. We use the Augmented Dickey-Fuller and Phillips-Perron stationarity tests in order to check real exchange deviations from PPP. Also, we investigate the existence of a connection between long-term between nominal exchange rate and industrial producer price indices from Romania and euro area. The main conclusions of this research highlight that PPP doesn't holds; real exchange rate stationarity tests doest not confirm the stationarity, thus between the aforementioned three variables it doesn't exists any equilibrium relation.
Keywords: F31; C32; E31; 330; purchasing power parity; real exchange rate; stationarity; cointegration Romania